Study of molecule variations in human xanthelasma skin based on confocal micro‐raman spectroscopy. Issue 5 (17th May 2015) - Qiu, Xuejun; Xiong, Ke; Ye, Xiangping; Huang, Zhitong; Chen, Ying; Su, Chengkang; Zhuang, Zhengfei; Guo, Zhouyi; Liu, Songhao
Summary Confocal micro‐Raman spectroscopy was used to distinguish human xanthelasma skin (HXS) from the human normal skin (HNS). Results showed that intensive Raman peaks at 1, 269, 1, 336, 1, 448, and 1, 656 cm−1 increased obviously. Both 1, 269 and 1, 656 cm−1 peaks showed that the proteins in HXS were mostly in the anti‐parallel ß sheet conformation. While the intensities of bands at 1, 032, 1, 087, 1, 300, and 1, 448 cm−1 belonged to lipids were enhanced in HXS spectrum compared to those in HNS spectrum. There were main intercellular lipids alkyl chains with minor proteins contribution at 1, 087 cm−1 and phenylalanine at 1, 032 cm−1. To quantitative analysis of the difference, the ratio of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgkv83bdzk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />I852/I829</alternatives> was calculated, which was 1:1.04 ± 0.04 and 1:1.11 ± 0.02 for HNS and HXS (p < 0.01), respectively. The data indicated that some tyrosine residues, which form a hydrogen bond with H2O prior to aggregation, were captured by strong hydrogen‐bond acceptors in the aggregate. The decreased ratio of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgkv83bdx2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />I852/I829</alternatives> indicated more hydrophobic in HXS than HNS. Principal component analysis showed a one‐to‐one relationship between human xanthelasma skin and the corresponding Raman spectra. It could be given useful help for the diagnostication of xanthelasma. SCANNING 37:307–312, 2015. © 2015 Wiley Periodicals, Inc.